Caesarean section as an informed choice in the UK: a systematic review. (2nd October 2021) - Djatmika, Clementine; Lusher, Joanne; Meyrick, Jane; Byron-Daniel, James
Abstract : Background: Despite the steady increase in the number of women giving birth via caesarean section in the UK, little is understood about how shared decision making is implemented in obstetrics or what this means for women that have given birth via caesarean. The aim of this review is to assess narratives of women's experiences of caesarean birth as an informed choice and their involvement in this process. Methods: A number of databases were searched, including MEDLINE via EBSCO, EMBASE via OVID, MIDIRS via OVID, Scopus, Wiley Online Library, Google Scholar and Ethos, as well as the reference sections of the included studies. Primary studies published between 1990–2020 were included and quality was assessed using the critical appraisal skills programme tool. Findings were analysed using a thematic synthesis framework to elicit higher order interpretations. Results: A total of 11 studies were included in the final review. Quality assessment indicated the studies were generally of good quality, with the main limitations being in methodology quality indicators. Thematic synthesis identified eight subthemes within three main themes: 'patient-doctor relationships', 'decision making as an emotional journey' and 'caesarean not really an informed "choice"'. The role of healthcare providers in promoting women's agency via patient-centred care was a prominent theme in women's narratives. Conclusions: Women's decision making in consent to undergo caesarean births is a complex, emotionally driven process that can have a significant long-term psychological impact.